Periapical Repair Following Endodontic Surgery: Two- andThree-Dimensional Imaging Evaluation Methods - Jorge, Érica Gouveia; Tanomaru-filho, Mario; Guerreiro-tanomaru, Juliane Maria; Reis, José Maurício Dos Santos Nunes; Spin-neto, Rubens; Gonçalves, Marcelo (Fundação Odontológica de Ribeirão Preto, 2015)
This study quantitatively assessed the periapical bone repair following endodonticsurgery, using planimetric evaluation based on two- (conventional and digitalintraoral radiographic images - IRs) and three-dimensional (cone beam computedtomography - CBCT) evaluation. Eleven maxillary anterior teeth (of 11 patients) withperiapical bone lesions and indication for surgical endodontic treatment wereselected. IRs and CBCT images were acquired before the endodontic surgery, and 48 h,4, and 8-months after the surgery. In each period of evaluation, the area (mm2) of the bone lesion was measured in the images, and the values forthe three methods were compared. The area in the CBCT images was measured in themesio-distal sections comprising the largest diameter of the lesion. Data weresubmitted to repeated measures 2-way ANOVA and t-tests with Bonferroni correction.There was significant difference between the periods of evaluation(p=0.002) regarding the assessed periapical bone lesion area. There was nostatistically significant difference between the methods of evaluation (p=0.023). In the CBCT images the lesion areas were 10% largerthan those observed in the conventional IRs (22.84 mm2) and 15% largerthan those observed in the digital IRs (21.48 mm2). From the baseline(40.12 mm2) to 4 (20.06 mm2) and 8-months (9.40mm2), reductions of 50 and 77% in the lesion area, respectively, wereobserved (p<0.0001). From 4 to 8-months, this value was 53%. Progressive bonerepair could be seen from 48h to 8-months following endodontic surgery based on two-(conventional and digital IRs) and three-dimensional (CBCT) evaluation. CBCT imageprovided results similar to those assessed by means of IRs.

Este estudo avaliou quantitativamente a reparação óssea periapical após cirurgiaparendodôntica, utilizando avaliação planimétrica bidimensional (imagenconvencionais e digitais intraorais radiográficas-IRs) e tridimensional (CBCT). Onzedentes anteriores da maxila (de 11 pacientes) com lesões ósseas periapicais eindicação de tratamento endodôntico cirúrgico foram selecionados. IRs e imagentomográficas foram obtidas antes da cirurgia parendodôntica, e 48 h, 4 e 8 meses apóa cirurgia. Para cada período, a área (mm2) de rarefação óssea foimensurada, e os valores para os três métodos comparados. A área nas imagens de CBCTfoi mensurada nas seções mésio-distal, compreendendo o maior diâmetro da lesão. Odados foram submetidos à análise de variância de medidas repetidas a dois critérios eteste T com correção de Bonferroni. Houve diferença significativa entre o períodos de avaliação (p=0,002) em relação à área de lesão ósseaperiapical mensurada. Não houve diferença significativa entre os métodos de avaliação(p=0,023). Nas imagens tomográficas as áreas das lesões foram 10% maiores do que aobservados nas IRs convencionais (22,84 mm2) e 15% maior do que àqueladas digitais (21,48 mm2). A partir dos valores baseline(40,12 mm2) a 4 (20,06 mm2) e 8 meses (9,40 mm2),foram observadas reduções de 50 e 77%, respectivamente, na área das lesõe(p<0,0001). De 4 a 8 meses, esse valor foi de 53%. Entre o período de 48h a oitomeses após as cirurgias parendodônticas foram observadas reparações ósseaprogressivas nas avaliações bidimensionais (IRs convencional e digital) etridimensional (CBCT). A CBCT produziu resultados semelhantes aqueles avaliados pormeio das IRs.
Keywords: Bone repair; radiography; computed tomography; diagnosis; endodontics